2020
DOI: 10.22201/ia.01851101p.2020.56.01.06
|View full text |Cite
|
Sign up to set email alerts
|

STAR FORMATION RATE IN LATE-TYPE GALAXIES: I- THE Hα AND FUV INTEGRATED VALUES

Abstract: The star formation rate (SFR) was determined from a sample of 36 late-type galaxies (14 dS and 22 Sm), from the SFR(H α ) and far ultraviolet (FUV) flux. We found that the SFR(FUV) is higher in most cases, larger for Sm galaxies and smaller for barred galaxies, for any morphological type, in both diagnostic methods. In addition, a study of the spatial distribution of star formation within these galaxies was made. We concluded that there is no preferential place for the star formation. Finally, we studied the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
(107 reference statements)
3
3
0
Order By: Relevance
“…. This assumption agrees with the conclusion of [4], where the authors, based on a small sample of late-type galaxies (14 dS and 22 Sm) inferred that "dS are forming a larger number of stars per area than Sm, despite the fact that the latter on average has twice more gas mass than dS."…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…. This assumption agrees with the conclusion of [4], where the authors, based on a small sample of late-type galaxies (14 dS and 22 Sm) inferred that "dS are forming a larger number of stars per area than Sm, despite the fact that the latter on average has twice more gas mass than dS."…”
Section: Discussionsupporting
confidence: 89%
“…A more detailed comparison of star formation rate of dwarf galaxies possessing spiral arms (dS) and without spirals (Sm) was presented by [4]. There the authors concluded that Sm galaxies have higher star formation rate values (SFR) than dS, however when the surface density of SFR is considered, both types of galaxies are indistinguishable.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the SFR in a galaxy speeds up the rate of gas consumption, thereby facilitating the transition from star forming to quenched. An increase in SFR in barred galaxies has been observed before (Alonso-Herrero & Knapen 2001;Hunt et al 2008;Ellison et al 2011;Coelho & Gadotti 2011;Hirota et al 2014;Janowiecki et al 2020;Magaña-Serrano et al 2020;Lin et al 2020). However, we conclude that, on average, only strong bars in SF galaxies help to quench their host through secular evolution.…”
Section: Strong Bars In Star Forming Galaxies Facilitate Quenchingsupporting
confidence: 49%
“…The simulations of Athanassoula et al (2013) have demonstrated that bars tend to form later if the gas fraction is high. Some observations show higher SFE/SFR in barred regions (Alonso-Herrero & Knapen 2001;Hunt et al 2008;Coelho & Gadotti 2011;Hirota et al 2014;Janowiecki et al 2020;Magaña-Serrano et al 2020;Lin et al 2020), while others observe lower SFR/SFE (Momose et al 2010;Yajima et al 2019;Maeda et al 2020). Sheth et al (2000) has shown a lower SFR in the region between the centre and bar ends, but higher in the very centre.…”
Section: Introductionmentioning
confidence: 96%
“…A more detailed comparison of star formation rate of dwarf galaxies possessing spiral arms (dS) and without spirals (Sm) was presented by Magaña-Serrano et al (2020). They concluded that Sm galaxies have higher star formation rate values (SFR) than dS, however when the surface density of SFR is considered, both types of galaxies are indistinguishable.…”
mentioning
confidence: 99%